THE ROLE OF GIS AND REMOTE SENSING IN MAPPING THE DISTRIBUTION OF GREENHOUSE GASES - Al-Mahdi, Ambare Muhammed; Maina, Muhammed Lawan (European Scientific Journal, ESJ, 2013)
Technology offers a means to assess, plan, and implement sustainable programmes that can affect us into the future. A GIS-based framework helps gain a scientific understanding of the earth at a truly global scale. GIS with updated data helps people to know what happens in our planet, how climate takes place and where impacts of climate change affect people. Remote sensing was also identified as a foundational technology. Tying in remote sensing technologies and data with GIS is a powerful combination of understanding spatial patterns in the earth’s ever changing surface. Combining Remote sensing information in a GIS allows us to track, model, and observe climate trends across the planet’s surface. (Jack Dangermond, 2010).